DIETARY INTAKE AND SUN EXPOSURE RELATED TO VITAMIN D CONCENTRATION IN THALASSEMIA PATIENTS: A LITERATURE REVIEW - Yesi Herawati; Gaga Irawan Nugraha; Dida Akhmad Gurnida (Universitas Airlangga, 2021)
Vitamin D has an important role in calcium homeostasis and bone minerals during rapid growth periods. Several studies have shown that deﬁciency of vitamin D occurs in thalassemia patient. The study used literature review to determine relation of dietary intake and sun exposure with vitamin D concentration in thalassemia patiens in 29 literatures. Those literatures were taken from books and articles published from 2010 to 2019 with the keywords “thalassemia”, “dietary intake”, “sun exposure” and “vitamin D” using database in Pubmed, Google Scholar and Medline. The results of 29 literatures showed that vitamin D deﬁciency is caused by reduced dietary intake and impaired vitamin D hydroxylation in the liver due to hemochromatosis resulting in high serum ferritin. Source of vitamin D comes from endogenous synthesis with sunlight exposure and little dietary source of vitamin D2 and vitamin D3. Another food intake can also aﬀect serum vitamin D concentration, mainly fat and protein intake. Vitamin D is fat soluble vitamin, it can be stored in the fat for later metabolized in the liver. Protein is required to transport vitamin D to blood circulation, enzyme formation and vitamin D receptor (VDR). Thalassemia patients need to increase of macro and micronutrients requirement. Low Hb concentration causes fatigue, tired easily and decreased appetite. A lot of research on thalassemia children found that intake of energy and protein were lower than recommended and lack of sun exposure. These conditions will aﬀect to vitamin D concentration. A comprehensive understanding in the relationship of dietary intake and sun exposure to vitamin D concentration in thalassemia patients is explained in this mini review. Maintaining normal vitamin D concentration through adequate dietary intake and sun exposure are very important to optimize growth in thalassemia patients.